Ebola as an Emerging and Re-Emerging Disease in Africa: Its Conceptual Frame Work and the Missing Link - Agharese, Efe-Aigbovo; Fidelis , Uchendi Okafor (NIGERIAN JOURNAL OF HEALTH PROMOTION, 2016)
Ebola has been identified as one of the emerging and re-emerging diseases in Africa. The present paper discusses its conceptual framework and the missing link under: Ebola concept and its historical background, Signs and symptoms, the risk factors, transmission mode, preventive and control measures and the treatment options which are operating primarily as supportive management in nature presently rather than offering curative treatment modalities. Proactive activities rather than complacency towards preventing and controlling Ebola infections should be highly encouraged to avoid re-emerging of the disease in African countries